A Proposed Method of Photovoltaic Solar Array Configuration Under Different Partial Shadow Conditions - Ali Mahmood, Humada; Hojabri, Mojgan; Mortaza, Mohamed (2014)
The benefit of improving the efficiency of photovoltaic(PV) solar system has come into view because of increasing the demand for electricity, especially in the urban areas. However, these PV solar systems are vulnerable to the mismatch operating conditions. Under such conditions, the performance of solar cells decreases rapidly since the non—uniform insolation hitting the cell sand with different values. Then this leads to cause rapidly decreasing in the output power value and maximum power point, beside to hot spot points that may be occur on the solar cell which finally leads to damage these cells. This paper proposes an optimal connection of sub strings with different value of shadow conditions, based on a thorough configuration that can significantly reduce that non—uniform conditions loss. The refinement over existing photovoltaic (PV) solar array interconnections is proven by extensive simulation results by using MATLAB SIMULINK.